Mechanism Analysis of the Influence of Freeze-Thaw on the Damage and Debonding Evolution of Sandstone-Concrete Interface - Yanjun Shen; Tao Luo; Xin Wei; Xueting Li; Long Jin; Liangdong Wen; Hui Peng; Yanjun Ji (Geofluids)
During tunnel construction in cold regions, the good adhesion of surrounding rock-lining interface is one of the important preconditions to evaluate the durability of tunnel lining. However, the repeated fatigue damage between rock and concrete due to the freeze-thaw action leads to debonding at the interface, which significantly affects the protective effect of shotcrete. Accordingly, based on the combination of sandstone-concrete as the object, through the development of sandstone-concrete interface freeze-thaw cycling test, and combining the nuclear magnetic resonance (NMR) test and scanning electron microscopy (SEM) analysis, the mechanism of debonding by freeze-thaw damage at the sandstone-concrete interface was systematically revealed. The conclusions drawn are as follows: (1) With the increase of freeze-thaw times, the content of micropores and macropores at the interface gradually increases, while the content of mesoporous gradually decreases. At the same time, the decrease of freeze-thaw temperature also aggravates the growth of interface cracks, and the freeze-thaw damage of interface is closely related to the minimum freeze-thaw temperature. (2) The damage of the sandstone side becomes more serious under multiple freeze-thaw actions. Concrete as a water retaining plate inhibits the migration of water to its interior, and a pot cover effect exists at the interface to provide better storage space for water accumulation. (3) The C-S-H group is the main source of the bond force of sandstone-concrete interface, and the freeze-thaw effect aggravates the fracture of the C-S-H group, which leads to the interface debonding. This study could provide an experimental basis and theoretical support for systematically recognizing the evolution mechanism of freeze-thaw damage and debonding of shotcrete in tunnels in cold regions.